2013
DOI: 10.1016/j.vhri.2013.02.009
|View full text |Cite
|
Sign up to set email alerts
|

Cost-Effectiveness of Clinical Pharmacy Education on Infection Management among Patients with Chronic Kidney Disease in an Indonesian Hospital

Abstract: Treatment of CKD stages 4 and 5 with CPE was more effective and cost-effective compared with treatment of CKD stages 4 and 5 without CPE. The ICERs indicated that extra costs were required to increase life saved in both stages.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 24 publications
0
7
0
Order By: Relevance
“…However, many studies proved that counseling and clinical pharmacy education on management of few diseases improved the outcomes and decreased the treatment costs. A quasi-experimental study conducted on patients with chronic kidney disease in an Indonesian hospital indicated that management of the disease with education was more cost-effective compared to those without education [17].…”
Section: Discussionmentioning
confidence: 99%
“…However, many studies proved that counseling and clinical pharmacy education on management of few diseases improved the outcomes and decreased the treatment costs. A quasi-experimental study conducted on patients with chronic kidney disease in an Indonesian hospital indicated that management of the disease with education was more cost-effective compared to those without education [17].…”
Section: Discussionmentioning
confidence: 99%
“…Studies suggest that clinical pharmacy education sessions had positive impacts on the management of CKD and that the cost expended on educational sessions are warranted to improve patient outcomes. 33 One of the strengths to this study is that it is based on the use of a theoretical framework. Using theory within healthcare research is developing at pace and is leading to enhanced robustness and rigour.…”
Section: Discussionmentioning
confidence: 99%
“…A study was conducted to evaluate the impacts of clinical pharmacy education (CPI) on outcome and costs in the management of infection among patients with chronic kidney disease Stages 4 and 5 in Haji Adam Malik Hospital, Indonesia. It was found that management of the patients with CPI was more cost-effective compared to those without CPI [17].…”
Section: Discussionmentioning
confidence: 99%